GAYA KEPEMIMPINAN TRANFORMASIONAL DALAM UPAYA PENINGKATAN PROFESIONAL GURU - Siti Nurjanah; Vitri Astuti; Pina Indah Sayekti; Anam Sutopo; Sabar Narimo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to analyze the application of transformational leadership styles in efforts to enhance teacher professionalism at MI Muhammadiyah Karanganyar. Transformational leadership, characterized by idealistic influence, inspirational motivation, intellectual stimulation, and individual consideration, is believed to positively impact the educational environment. This research uses a qualitative approach with descriptive and case study designs. Data were collected through observation, in-depth interviews, and documentation. The results show that the principal at MI Muhammadiyah Karanganyar possesses characteristics of a transformational leader, such as being a role model, motivating teachers, encouraging innovation, and providing personal attention. The implementation of this leadership style has increased teacher professionalism through training programs, performance evaluations, team collaboration, and constructive feedback. In conclusion, transformational leadership plays a significant role in creating an environment that supports the development of teacher professionalism and the overall improvement of educational quality.